TRADE AND SUSTAINABILITY OF ASEAN FISHERIES RESOURCES (Journal of Economics and Sustainability, 2019)
Fisheries trade is crucial to a country as it provides employment and income for the fishers and person indirectly involved in fisheries. The objective of fisheries trade is to provide opportunities to fishers to reach wider markets and obtain greater value for their produce.   Extensive catch of fisheries stocks is carried out to increase the trade in fisheries products especially in ASEAN countries where there is a high demand for fish with trade liberalisation.  The large harvesting of fisheries resources may result in the depletion of fisheries resources.  ASEAN will face the problem of sustainability of fisheries resources in the long run if the large harvesting of fisheries resources is not managed with sustainability as an important goal.  One way of reducing the depletion of fisheries resources and ensuring adequate fish for future consumption is to develop sustainability standards for fisheries and fisheries products.  This paper focuses on fisheries standards for managing fisheries in ASEAN countries and addresses the problems faced by small-scale fishers and governments in implementing the standards.  Moreover, this paper suggests ways to ensure the sustainability of fisheries resources in the future.